2017
DOI: 10.15561/20755279.2017.0303
|View full text |Cite
|
Sign up to set email alerts
|

Determination of first year students’ physical condition and physical fitness level

Abstract: Purpose:to study and find out first year students' physical condition and physical fitness levels. Material:n the research first year students (n=86) participated. The age of the participants was 16 -19 years. They passed the following tests for physical fitness: 100 meters' run; run during 12 minutes; long jump from the spot; chin ups; torso rising from lying to sitting position during 1 minute; forward torso bending from sitting position, cm. Results:it was found that 41% of students have low and below avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…Besides, the high level of variability for such indices as the strength of the upper limbs and flexibility demonstrates the necessity to divide the girls into subgroups while developing the corresponding physical features or the necessity for them to attend additional PE classes of various types. The conducted studies of female students' physical fitness confirmed and supplemented the findings by Osipov, Kudryavtsev, Iermakov, Yanova, Lepilina, Plotnikova, and Dorzhieva (2017), Kashuba et al (2017) and Fotynyuk (2017).…”
Section: Discussionsupporting
confidence: 63%
“…Besides, the high level of variability for such indices as the strength of the upper limbs and flexibility demonstrates the necessity to divide the girls into subgroups while developing the corresponding physical features or the necessity for them to attend additional PE classes of various types. The conducted studies of female students' physical fitness confirmed and supplemented the findings by Osipov, Kudryavtsev, Iermakov, Yanova, Lepilina, Plotnikova, and Dorzhieva (2017), Kashuba et al (2017) and Fotynyuk (2017).…”
Section: Discussionsupporting
confidence: 63%
“…Physical exercises conducted in higher educational establishments do not provide the students with the necessary amount of motor activity [11,12]. Their volume is 4 hours per week, which does not correspond to the biological standard of a young person [13].…”
Section: Introductionmentioning
confidence: 99%
“…There are many experts who recommend to increase the amount of physical activity of the modern students. You can do this through additional physical education or sports activities in your spare time (Fotynyuk, 2017). The students who are regular participants in various sporting events have higher rates of physical development, they are physically attractive and have a lower fat content in the total body weight than students who do not engage in active sports activities (Campos, Marques, Silva, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the colleges and universities in England and Wales, despite significant measures to support the physical activity of the students, the participation rates of young people in various sports and sports activities are not acceptable (Boccaro, Kanters, Cerin, et al, 2012). Indeed, many experts say that there is a clear negative trend of lack of attention to physical exercises among the modern students (Osipov, Kudryavtsev, Fedorova, et al, 2017;Fotynyuk, 2017). Thus, the administration of educational institutions faces the difficult task of significantly increasing the level of motor activity of students in the context of a decrease in the interest of young people in sports and sports activities.…”
Section: Introductionmentioning
confidence: 99%